2006
DOI: 10.1080/00016480500529314
|View full text |Cite
|
Sign up to set email alerts
|

Laryngopharyngeal reflux finding scores correlate with gastroesophageal reflux disease and Helicobacter pylori expression

Abstract: The mean RFS of the whole population was 11.5+/-4.4. The mean RFS of patients who had lower esophageal mucosal inflammation was 7+/-0.1, 8.1+/-1.3, 13.9+/-3.7, and 16.6+/-3.5, for grades A, B, C and D, respectively. The RFS of patients according to HP expression was as follows: 7.2+/-0.4, 9.3+/-3.07, 12.7+/-3.16, and 17.8+/-2.1, for normal (score 0), score I, score II, and score III, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Other studies have also found that the most common laryngeal finding "as assessed by RFS" was found to be erythema/hyperemia like studies of Book et [13,14,[21][22][23][24]. Also, other authors have noted that the most common laryngoscopic signs are posterior commissure hypertrophy as by Belafsky et al and partial ventricular obliteration as by Tezer et al [11,25].…”
Section: Discussionmentioning
confidence: 86%
“…Other studies have also found that the most common laryngeal finding "as assessed by RFS" was found to be erythema/hyperemia like studies of Book et [13,14,[21][22][23][24]. Also, other authors have noted that the most common laryngoscopic signs are posterior commissure hypertrophy as by Belafsky et al and partial ventricular obliteration as by Tezer et al [11,25].…”
Section: Discussionmentioning
confidence: 86%
“…The mean RFS score was 9.5 in our study and more than 7 score was considered abnormal. In a study done by Tezer et al 16 , the mean RFS score was 11.5. Similarly mean score was recorded to be 10 in a study by Vardar et al 2 .…”
Section: Discussionmentioning
confidence: 91%
“…The most common presenting symptoms in our study was hoarseness (97%) followed by coughing (90.7%). The mean RSI score was 11.6±2.2 (range, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The distribution of severity of each symptom among the patients was summarised in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…En cuanto a la correlación de Helicobacter pylori y laringitis por RLF, Taner y colaboradores (23) y Tezer y colaboradores (24) han concluido que la expresión de positividad de Helicobacter pylori y el grado de ERGE se correlacionaron con RLF en 45 pacientes. La positividad de Helicobacter pylori y el grado de ERGE fueron más adversos en pacientes con RLF.…”
Section: Discussionunclassified